Negative density dependence characterizes mutualistic interactions between birds and fruiting plants across latitudes - Carlo, Tomás A.; Messeder, João Vitor S.; Espíndola, Wálter D.; Vizzachero, Benjamin S.; Boyer, Brady W.; Hernández-Mejía, Jacqueline; Torres-Páucar, E. Adrián; Fontanella, Antonio [UNESP]; Pizo, Marco A. [UNESP]; Amico, Guillermo; Salinas, Letty; Arana, César; et al. (The Royal Society, 2024)
Negative density dependence (NDD) in biotic interactions of interference such as plant-plant competition, granivory and herbivory are well-documented mechanisms that promote species' coexistence in diverse plant communities worldwide. Here, we investigated the generality of a novel type of NDD mechanism that operates through the mutualistic interactions of frugivory and seed dispersal among fruit-eating birds and plants. By sampling community-wide frugivory interactions at high spatial and temporal resolution in Pennsylvania, Puerto Rico, Peru, Brazil and Argentina, we evaluated whether interaction frequencies between birds and fruit resources occurred more often (selection), as expected, or below expectations (under-utilization) set by the relative fruit abundance of the fruit resources of each plant species. Our models considered the influence of temporal scales of fruit availability and bird phylogeny and diets, revealing that NDD characterizes frugivory across communities. Irrespective of taxa or dietary guild, birds tended to select fruits of plant species that were proportionally rare in their communities, or that became rare following phenological fluctuations, while they mostly under-utilized abundant fruit resources. Our results demonstrate that negative density-dependence in frugivore-plant interactions provides a strong equalizing mechanism for the dispersal processes of fleshy-fruited plant species in temperate and tropical communities, likely contributing to building and sustaining plant diversity. This article is part of the theme issue 'Diversitydependence of dispersal: interspecific interactions determine spatial dynamics'.
Keywords: antiapostatic; density dependence; diversity maintenance; foraging; frugivory; seed dispersal